EFFECTIVENESS OF AUDIOVISUAL HEALTH EDUCATION IN IMPROVING KNOWLEDGE OF JUVENILE DELINQUENCY AMONG MIDWIFERY STUDENTS - Ahdatul Islamiah; Tarsikah Tarsikah; Domas Nurchandra Pramudianti (Poltekkes Kemenkes Pontianak, 2026)
Juvenile delinquency remains a significant public health and social concern that adversely affects adolescents' physical, psychological, and social well-being. Increasing exposure to negative environmental influences underscores the importance of effective educational strategies to improve adolescents' knowledge of delinquent behaviors and their consequences. Audiovisual educational media have emerged as an innovative health promotion approach because they integrate visual and auditory stimuli, thereby enhancing comprehension and information retention. This study aimed to determine the effect of audiovisual educational media on knowledge regarding juvenile delinquency among first-year midwifery students at Poltekkes Kemenkes Surabaya. A pre-experimental study with a one-group pretest–posttest design was conducted involving 159 respondents selected through purposive sampling. Participants completed a structured questionnaire before and after receiving an audiovisual educational intervention on juvenile delinquency. Data were analyzed using descriptive statistics and the Wilcoxon Signed Rank Test with a significance level of 0.05. Before the intervention, most respondents demonstrated poor knowledge regarding juvenile delinquency; however, following the intervention, the majority achieved good knowledge levels. The mean knowledge score increased from before the intervention to after the intervention, with statistical analysis revealing a significant difference between pretest and posttest scores (p < 0.001). These findings indicate that audiovisual educational media effectively improve knowledge regarding juvenile delinquency among midwifery students. Integrating interactive audiovisual learning into adolescent health promotion programs may enhance learning outcomes, strengthen the educational competencies of future midwives, and contribute to more effective juvenile delinquency prevention strategies.